The aggregate index of systemic inflammation (AISI): a novel predictor for hypertension - Xiu, Jiaming; Lin, Xueqin; Chen, Qiansheng; Yu, Pei; Lu, Jin; Yang, Yanfang; Chen, Weihua; Bao, Kunming; Wang, Junjie; Zhu, Jinlong; Zhang, Xiaoying; Pan, Yuxiong; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective: Inflammation plays an important role in the pathophysiology of hypertension (HTN). Aggregate index of systemic inflammation (AISI), as a new inflammatory and prognostic marker has emerged recently. Our goal was to determine whether there was a relationship between HTN and AISI. Methods: We analyzed patients with HTN from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. The primary end point was cardiovascular mortality. A total of 23,765 participants were divided into four groups according to the AISI quartile level. The association between AISI and cardiovascular mortality in patients with HTN was assessed by survival curves and Cox regression analyses based on NHANES recommended weights. Results: High levels of AISI were significantly associated with cardiovascular mortality in patients with HTN. After full adjustment for confounders, there was no significant difference in the risk of cardiovascular mortality between groups Q2 and Q3 compared with group Q1, and group Q4 (HR: 1.91, 95% CI: 1.42-2.58; P<0.001) had a higher risk of cardiovascular mortality. Results remained similar in subgroup analyses stratified by age (P for interaction = 0.568), gender (P for interaction = 0.059), and obesity (P for interaction = 0.289). Conclusions: In adults with HTN, elevated AISI levels are significantly associated with an increased risk of cardiovascular mortality and may serve as an early warning parameter for poor prognosis.